Tax Effort in Sub-Saharan Africa - Stotsky, Janet (IMF Working Papers; Working Paper ;, 1997)
Many sub-Saharan African countries face difficulty in raising tax revenue for public purposes. This study uses panel data on 43 sub-Saharan African countries during 1990-95 to measure the determinants of the tax share in GDP and to construct a measure of tax effort. The analysis suggests that the countries with a relatively high tax share tend to have a relatively high index of tax effort, although these results are not uniform across the countries. The results can be used to provide guidance on to the proper mix of fiscal policy in the event of budgetary imbalance.